ANALISIS DAMPAK KEBIJAKAN PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA SAMPAH (PLTSA) TEMPAT PEMBUANGAN AKHIR (TPA) PUTRI CEMPO KOTA SURAKARTA - Ardiansyah, Reza; Marom, Aufarul; Nurcahyanto, Herbasuki (Journal of Public Policy and Management Review, 2024)
Waste is a fundamental problem that occurs in almost all cities in Indonesia. The increasingly narrow land followed by high population growth has resulted in increasing waste generation, including in Surakarta City. In response to this, the Surakarta City Government built the Putri Cempo Waste Disposal Site (TPA) Waste Power Plant (PLTSa) to solve the waste problem in Surakarta City. However, the policy has not been able to solve the waste management problem completely and create environmental impacts for the surroundings. This research aims to analyze the impacts of the Putri Cempo PLTSa development policy in Surakarta City. The method used in this research is descriptive qualitative with data collection techniques through interviews, observation, documentation, and literature study. The research used Finsterbusch and Motz's Environmental Impact Evaluation Theory. The results showed that there was an environmental impact in the form of TAR in the Putri Cempo PLTSa development policy which was still within reasonable limits of environmental quality standards so that it could still be controlled by the manager. Suggestions that can be conveyed in the research are optimizing the function of waste banks through sorting household waste and utilizing organic waste into compost and briquettes at the household level.